Bibliometric Analysis of Global Research Trends on Language Proficiency Tests (2018–2025) - Nursipah Hidayah; Achmad Ridwan; Sugeng Priyanto; Irwanto; Riyan Arthur (Indonesian Journal of Instruction, 2026)
Mastery of foreign languages, especially English, is a crucial competency in both the educational and professional worlds, especially the Language Proficiency Test (LPT). This study aims to analyze trends, intellectual structures, and the direction of global research development related to the Language Proficiency Test (LPT) in the period 2018–2025. The method used is a quantitative bibliometric approach based on data from Scopus, with analysis using Bibliometrix (R-package) and VOSviewer software. A total of 193 scientific articles were analyzed based on publication productivity, author and country collaboration, and keyword relevance. The results show that LPT studies experience publication growth of 6.58% per year with an international collaboration rate of 12.44%. Dominant themes in this study include validity, reliability, assessment, EFL learners, and washback. The thematic map shows that current research focuses on technical aspects of testing such as item response theory and construct validity, while new themes such as AI-based testing, remote proctoring, and feedback learning are emerging as future directions. This study emphasizes the importance of valid, fair, and adaptive language proficiency testing to technological developments and the global social context.